(f-g)(x) = f(x) - g(x) = 3^x + 10x - (4x - 2) = 3^x + 6x + 2 Answer
Answer:
37
Step-by-step explanation:
Answer:
- 4.7
Step-by-step explanation:
Step 1:
c - 1.5 + 6.8 = 0.6
Step 2:
c + 5.3 = 0.6
Step 3:
c = 0.6 - 5.3
Answer:
c = - 4.7
Hope This Helps :)
Answer:
Relate the points down below to yourself and give examples
Step-by-step explanation:
You show confidence and leadership
Being yourself/unique
You speak and interact kindly with everyone
You show respect and concern for others
You give advice to those who need it
You have humility and a willingness to admit mistakes.
You do good things outside of school
23.9 is the discount so you gonna round it up so get an whole number the answer is 24